Factors impacting job satisfaction among pharmacists in the Arab world: A qualitative study - Ali Azeez Al-Jumaili; Rehab Elhiny; Dixon Thomas; Fawzy Elbarbry; Maher Khdour; Fatima Sherbeny; Anas Hamad (Saudi Pharmaceutical Journal, 2023)
Purpose: This study was undertaken to investigate in-depth the factors impacting job satisfaction among pharmacists in the Arab world and the challenges they encounter in their career path. The outcome of this study should help the local policymakers to take corrective actions to improve pharmacist’s satisfaction and therefore enhance quality of patient care. Method: This qualitative study collected responses of pharmacists from 12 Arab countries, as part of a large quantitative survey. Participants added comments to an optional open-ended question regarding work satisfaction. The Qualtrics Survey Software was used to collect the responses. The survey was distributed from March to May 2021 through multiple online channels for filling. The responses collected were analysed to develop themes. An inductive constructivist approach was used for the conceptual thematic analysis as the methodological orientation. Results: A total of 110 responses/comments were received from the study participants. The two largest practice settings of the participants were from hospitals (44.5%) and community pharmacies (28.2%). Almost 40% of responses came from pharmacists practising in Qatar (21.8%) and UAE (18.1%). The survey data demonstrated several reasons impacting job satisfaction among pharmacists practising in the Arab countries. Underestimation of the pharmacists' role, low salaries, lack of motivation and excessive workload were reported as major contributors to job dissatisfaction. On the other hand, professional commitment and the culture of the work setting were the major contributors to job satisfaction. Conclusions: The study provides valuable insights into the aspects concerning pharmacists’ satisfaction in the Arab world. Policymakers and other stakeholders need to act upon aspects of pharmacists’ job satisfaction and dissatisfaction to ensure potentially better working environment and patient outcomes.